The Intra- and Inter-rater Reliability of an Arm Care Screening Tool in High School Baseball Coaches - Kyle A. Matsel; Stephanie N. Brown; Matt C. Hoch; Robert J. Butler; Philip M. Westgate; Terry R. Malone; Tim L. Uhl (International Journal of Sports Physical Therapy, 2021)
# Background